High-purity silica sol and preparation method thereof

By using sodium-free organic catalyst alkyl lithium or alkoxy lithium initiator, the problems of uneven particle distribution and environmental pollution in the preparation of silica sol are solved, and the preparation of high-purity spherical silica sol is realized, with simple process and low Cost and good application prospects.

CN119176560APending Publication Date: 2024-12-24宁波大浦新材料科技有限公司 +2

Patent Information

Application Number
CN202411306457.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the existing preparation methods of silica sol, the ion exchange method leads to uneven particle size distribution and environmental pollution. Remaining sodium ion impurities in the one-step hydrolysis method of single-stage silicon powder makes it difficult to prepare high-purity spherical silica sol.

Method used

The sodium-free organic catalyst alkyl lithium or alkoxy lithium is used as the initiator to react silica acid by reacting silica powder with water, and polymerizing and concentrating to prepare a spherical silica sol without sodium.

Benefits of technology

The preparation of high-purity spherical silica sol has been achieved, with simple process, low cost, no environmental pollution, and good application prospects and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176560A_ABST
    Figure CN119176560A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of silica sol, and provides high-purity silica sol and a preparation method thereof. The method comprises the following steps: mixing a lithium source, silicon powder and a first part of water to carry out an initiation reaction, adding residual water after the initiation reaction is finished, and carrying out a polymerization reaction to obtain a first product; mixing the first product with an acid solution to obtain a mixed solution; and filtering the mixed solution, and concentrating the filtrate obtained by filtering to obtain the high-purity silica sol. The preparation method comprises the following steps: by taking lithium alkylide or lithium alkoxy as an initiator and monatomic silicon powder as a silicon source, reacting with water to generate silicic acid, and further polymerizing and concentrating to prepare the sodium-free and high-purity spherical silica sol with high additional value. The mass fraction of silicon dioxide in the spherical silica sol is 25-40%, the specific gravity at the temperature of 20 DEG C is 1.1-1.3 g / cm < 3 >, the viscosity at the temperature of 25 DEG C is 10-50000 cP, and the particle size is 10-20 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silica sol preparation, and in particular to a high-purity silica sol and a preparation method thereof. Background Art

[0002] Silica sol is a colloidal solution of colloidal silicon dioxide particles dispersed in water, and is a very important inorganic material. Since the surface of the silicon dioxide particles in the silica sol has a large number of hydroxyl groups, it has a high reactivity and is widely used in the fields of chemical industry, precision casting, textile, papermaking, coating, food, electronics, mineral processing, etc.

[0003] At present, the most mature and widely used preparation method of silica sol is the ion exchange method, which uses water glass (sodium silicate) as raw material. The water glass is treated with a cation exchange resin to obtain a mother liquor containing crystal nuclei, and then a dilute silicic acid solution is added to the mother liquor containing the crystal nuclei to control the growth rate of the crystal nuclei. Finally, the silica sol product is prepared through a concentration process. The silica sol particles prepared by the ion exchange method using sodium silicate as raw material will have problems such as unclear interfaces between particles, non-spherical and uncontrollable morphology, and uneven distribution of particle size. In addition to consuming sodium silicate, the preparation of silica sol by the ion exchange method also consumes hydrochloric acid solution or sulfuric acid solution for washing and regenerating the corresponding ion exchange resin, which will produce a large amount of salt-containing and acid-containing wastewater, causing environmental pollution and other problems.

[0004] Relatively speaking, the process of preparing silica sol by one-step hydrolysis of elemental silicon powder is relatively simple and is widely used in China. Unlike silica sol prepared by ion exchange method, silica sol particles prepared by direct hydrolysis of elemental silicon powder are denser and more uniform. Moreover, since pure silicon powder reacts with deionized water to directly generate silica sol, the prepared silica sol product also contains fewer impurity ions. The Chinese invention patent application with application number CN104326477A discloses a method for preparing ultra-high purity silica sol for capacitors. In the presence of an alkaline catalyst, the activated silicon powder reacts in an aqueous solution at 50-85°C for 2-24 hours, and after filtration and concentration, a silica sol with a silicon dioxide content of 5-35%, an average particle size of 8-30nm, and a morphology close to a spherical shape is obtained. The Chinese invention patent application with application number CN106145123A discloses a simple and quick method for preparing silica sol. In an aqueous sodium hydroxide solution containing anionic surfactant, industrial-grade silicon powder is reacted in an aqueous solution at 75-90°C for 1-2 hours, and a silica sol with a silicon dioxide content of 40-60% is obtained after filtration, separation and impurity removal.

[0005] However, whether it is the ion exchange method using sodium silicate as raw material or the one-step hydrolysis method of elemental silicon under the action of sodium-containing alkaline catalyst, a small amount of impurity sodium ions will inevitably remain in the silica sol, and the silica sol particles prepared are difficult to achieve a complete spherical morphology. Therefore, it is of great significance to provide a preparation method of spherical silica sol with simple preparation process, low cost, low environmental pollution and high product quality. Summary of the invention

[0006] The purpose of the present invention is to provide a high-purity silica sol and a preparation method thereof, in view of the defects that the silica sol prepared by the ion exchange method using sodium silicate as a raw material in the prior art has uneven particle size distribution and produces a large amount of salt-containing and acidic wastewater, or the deficiency that a small amount of sodium ion impurities remain in the silica sol prepared by the one-step hydrolysis method using elemental silicon powder as a raw material. Under the initiation of an organic catalyst alkyl lithium or alkoxy lithium, silicate is generated by the reaction of silicon powder with water, and further polymerization and concentration are performed to prepare a sodium-free high-purity spherical silica sol.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing high-purity silica sol, comprising the following steps:

[0009] (1) mixing a lithium source, silicon powder and a first portion of water to initiate a reaction, and adding remaining water after the initiation reaction to perform a polymerization reaction to obtain a first product;

[0010] (2) mixing the first product with an acid solution to obtain a mixed solution; filtering the mixed solution, and then concentrating the filtrate obtained by filtration to obtain the high-purity silica sol.

[0011] Preferably, the particle size of the silicon powder in step (1) is 100 to 600 mesh;

[0012] The lithium source is alkyl lithium or alkoxy lithium; the alkoxy lithium includes fatty alkyl alcohol lithium or polyethylene glycol lithium;

[0013] The mass ratio of the lithium source to the silicon powder is 0.5-5:100, and the mass ratio of the silicon powder to the first portion of water is 5-20:20-60.

[0014] Preferably, the initial temperature of the initiation reaction in step (1) is 60-80°C, the temperature is increased during the initiation reaction, the heating rate of the initiation reaction is 10-20°C / min, and the target temperature of the initiation reaction is 85-95°C.

[0015] Preferably, in step (1), the mass ratio of the first part of water to the remaining water is 20-60:40-80.

[0016] Preferably, the temperature of the polymerization reaction in step (1) is the same as the target temperature for initiating the reaction, and the polymerization reaction time is 2 to 10 hours.

[0017] Preferably, the acid solution in step (2) comprises one or more of hydrochloric acid solution, nitric acid solution and sulfuric acid solution;

[0018] The mass fraction of the hydrochloric acid solution is 8-33%, the mass fraction of the nitric acid solution is 30-70%, and the mass fraction of the sulfuric acid solution is 94-96%.

[0019] Preferably, the pH value of the mixed solution in step (2) is 0.5 to 4.5;

[0020] The concentration temperature in step (2) is 80-100° C., and the concentration vacuum degree is 0.06-0.1 mPa.

[0021] The invention also provides high-purity silica sol prepared by the preparation method of the high-purity silica sol.

[0022] Preferably, the mass fraction of silicon dioxide in the high-purity silica sol is 25-40%, and the specific gravity of the high-purity silica sol at 20°C is 1.1-1.3 g / cm 3 The viscosity of high-purity silica sol at 25°C is 10-50000 cP, and the particle size of high-purity silica sol is 10-20 nm.

[0023] The beneficial effects of the present invention are:

[0024] The present invention provides a method for preparing high-purity silica sol, comprising the following steps: mixing a lithium source, silicon powder and a first portion of water to initiate a reaction, adding the remaining water after the initiation reaction to perform a polymerization reaction to obtain a first product; mixing the first product with an acid solution to obtain a mixed solution; filtering the mixed solution, and then concentrating the filtrate obtained by filtration to obtain a high-purity silica sol. The present invention uses a sodium-free organic catalyst-alkyl lithium or alkoxy lithium as an initiator, and single silicon powder as a silicon source, and generates silicic acid by reacting with water, and further polymerizes and concentrates to prepare a high-value-added sodium-free high-purity spherical silica sol. The mass fraction of silicon dioxide in the spherical silica sol is 25-40%, and the specific gravity of the silica sol at 20°C is 1.1-1.3 g / cm 3 The viscosity of the silica sol at 25°C is 10-50000 cP, and the particle size of the silica sol is 10-20 nm. The preparation method of the invention has simple process, low production cost, no environmental pollution, easy industrialization, good application prospect and huge economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the specific preparation process of the high-purity silica sol in the present invention;

[0026] Figure 2 This is a scanning electron microscope characterization image of the high-purity silica sol in Example 1. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing high-purity silica sol, comprising the following steps:

[0028] (1) mixing a lithium source, silicon powder and a first portion of water to initiate a reaction, and adding remaining water after the initiation reaction to perform a polymerization reaction to obtain a first product;

[0029] (2) mixing the first product with an acid solution to obtain a mixed solution; filtering the mixed solution, and then concentrating the filtrate obtained by filtration to obtain the high-purity silica sol.

[0030] In the present invention, the lithium source in step (1) is preferably an alkyl lithium or an alkoxy lithium; the alkoxy lithium preferably includes a fatty alkyl alcohol lithium or polyethylene glycol lithium; the alkyl lithium is an alkyl derivative of lithium, and the general formula is RLi, wherein R is a linear or branched alkyl, cycloalkyl or aryl group; the alkyl lithium preferably includes methyl lithium, ethyl lithium, propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, pentyl lithium, hexyl lithium, cyclohexyl lithium, tert-octyl lithium, n-eicosyl lithium, phenyl lithium, methyl phenyl lithium, butyl phenyl lithium, naphthyl lithium or butyl cyclohexyl lithium, and more preferably methyl lithium, ethyl lithium, propyl lithium, n-butyl lithium, pentyl lithium or hexyl lithium; the structural formula of the fatty alkyl alcohol lithium is C n H 2n+1 OLi, the value of n is preferably 1 to 6, more preferably 2 to 5, and more preferably 3 to 4; the structural formula of the polyethylene glycol lithium is H(OC2H4) m The value of OLi,m is preferably 1-100, more preferably 2-99, and even more preferably 5-95.

[0031] In the present invention, the general reaction formula of fatty alkyl lithium alkoxide is:

[0032] C n H 2n+1 OH+RLi→C n H 2n+1 OLi+RH.

[0033] In the present invention, the general reaction formula of lithium polyethylene glycol is:

[0034] H(OC2H4) m OH+RLi→H(OC2H4) m OLi+RH.

[0035] In the present invention, the particle size of the silicon powder in step (1) is preferably 100-600 mesh, more preferably 200-500 mesh, and even more preferably 300-400 mesh.

[0036] In the present invention, the mass ratio of the lithium source to the silicon powder is preferably 0.5-5:100, more preferably 1-4:100, and more preferably 2-3:100; the mass ratio of the silicon powder to the first part of water is preferably 5-20:20-60, more preferably 7-15:25-50, and more preferably 10-12:30-40.

[0037] In the present invention, the mixing in step (1) preferably comprises the following steps: adding a lithium source to the first portion of water and stirring to obtain a lithium source solution; then slowly adding silicon powder to the lithium source solution under stirring conditions, stirring to obtain a uniform mixture, heating the mixture to an initial temperature for initiating the reaction, and initiating the reaction; the present invention does not specifically limit the stirring speed, and the stirring speed may be determined by conventional technical means.

[0038] In the present invention, when the lithium source is an alkyl lithium, the chemical formula of the initiation reaction in step (1) is:

[0039] Si+2RLi+5H2O→Si(OH)4+2H2+2LiOH+2HR.

[0040] In the present invention, the initial temperature of the initiation reaction in step (1) is preferably 60-80°C, more preferably 65-75°C, and more preferably 70°C; the temperature is increased during the initiation reaction, and the heating rate of the initiation reaction is preferably 10-20°C / min, more preferably 12-18°C / min, and more preferably 15-16°C / min; the target temperature of the initiation reaction is preferably 85-95°C, more preferably 88-92°C, and more preferably 90°C.

[0041] In the present invention, after the initiation reaction in step (1) is completed, that is, when the temperature is raised to the target temperature for initiating the reaction, the remaining water is slowly dripped into the system obtained by the initiation reaction under stirring to carry out a polymerization reaction (when water is dripped, the polymerization reaction starts). The polymerization reaction is an exothermic reaction. During the polymerization reaction, the temperature of the polymerization reaction is maintained at the target temperature for initiating the reaction by controlling the dripping speed of water.

[0042] In the present invention, the mass ratio of the first part of water to the remaining water in step (1) is preferably 20-60:40-80, more preferably 25-50:50-75, and more preferably 30-40:60-70.

[0043] In the present invention, the chemical formula of the polymerization reaction in step (1) is:

[0044] nSi(OH)4→HO(SiO2) n H+(n-1)H2O.

[0045] In the present invention, the temperature of the polymerization reaction in step (1) is the same as the target temperature for initiating the reaction, and the polymerization reaction time (polymerization reaction time refers to the total time from the start of adding water to the end of the polymerization reaction) is preferably 2 to 10 hours, more preferably 3 to 8 hours, and more preferably 4 to 6 hours.

[0046] In the present invention, after the polymerization reaction in step (1) is completed, the obtained system is naturally cooled to obtain the first product; the target temperature of the natural cooling is preferably 40 to 80°C, more preferably 50 to 70°C, and more preferably 60°C.

[0047] In the present invention, the acid solution in step (2) preferably includes one or more of hydrochloric acid solution, nitric acid solution and sulfuric acid solution.

[0048] In the present invention, the mass fraction of the hydrochloric acid solution is preferably 8-33%, more preferably 10-30%, more preferably 15-25%; the mass fraction of the nitric acid solution is preferably 30-70%, more preferably 40-60%, more preferably 50-55%; the mass fraction of the sulfuric acid solution is preferably 94-96%, more preferably 94.5-95.5%, more preferably 95%.

[0049] In the present invention, the pH value of the mixed solution in step (2) is preferably 0.5 to 4.5, more preferably 1 to 4, and even more preferably 2 to 2.5.

[0050] In the present invention, step (2) is to naturally cool the mixed solution, and the target temperature of the natural cooling is preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; then, the naturally cooled mixed solution is precipitated to separate the supernatant and the solid layer (i.e., the lower layer obtained by precipitation), and the supernatant and the lower layer obtained by precipitation are filtered independently, and the filtrates obtained by filtering the two are combined and concentrated to obtain the silica sol.

[0051] In the present invention, the concentration temperature in step (2) is preferably 80-100°C, more preferably 85-95°C, and more preferably 90°C; the concentration vacuum is preferably 0.06-0.1 mPa, more preferably 0.07-0.09 mPa, and more preferably 0.08 mPa.

[0052] In the present invention, the chemical formula of the concentration in step (2) is:

[0053] HO(SiO2) n H→nSiO2+H2O.

[0054] The specific preparation process diagram of the high-purity silica sol in the present invention is as follows: Figure 1 shown.

[0055] The invention also provides high-purity silica sol prepared by the preparation method of the high-purity silica sol.

[0056] In the present invention, the mass fraction of silicon dioxide in the high-purity silica sol is preferably 25-40%, more preferably 30-35%, and more preferably 32%; the specific gravity of the high-purity silica sol at 20°C is preferably 1.1-1.3 g / cm 3 , more preferably 1.15 to 1.25 g / cm 3 , more preferably 1.2 g / cm 3 The viscosity of the high-purity silica sol at 25°C is preferably 10 to 50,000 cP, more preferably 30 to 30,000 cP, and more preferably 40 to 25,000 cP; the particle size of the high-purity silica sol is preferably 10 to 20 nm, more preferably 12 to 18 nm, and more preferably 15 to 16 nm.

[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1

[0059] 120 g of water is added to a three-necked flask, and then 1 g of n-butyl lithium is added, and the mixture is stirred to obtain a lithium source solution; then, 50 g of silicon powder with a particle size of 200 to 300 meshes is slowly added to the alkyl lithium solution under a stirring condition of a rotation speed of 250 r / min, and the mixture is stirred to obtain a lithium source solution; the mixture is heated to 80° C. to initiate a reaction; the temperature is increased during the initiation reaction at a heating rate of 15° C. / min; when the temperature is increased to 90° C., the initiation reaction is terminated; under a stirring condition, 400 g of water is slowly dripped into the three-necked flask to perform a polymerization reaction; during the polymerization reaction, the temperature of the polymerization reaction is maintained at the target temperature of the initiation reaction by controlling the dripping speed of water; The polymerization reaction time (the total time from the start of water addition to the end of the polymerization reaction) is set to 4 hours. After the polymerization reaction is completed, the obtained system is naturally cooled to 60°C to obtain the first product; then a sulfuric acid solution with a mass fraction of 95% is added to the first product to obtain a mixed solution with a pH of 2.5, which is naturally cooled to 25°C. Then, the naturally cooled mixed solution is precipitated to separate the supernatant and the solid layer (i.e., the lower layer obtained by precipitation), the supernatant and the lower layer obtained by precipitation are filtered independently, the filtrates obtained by filtering the two are combined, and concentrated at a temperature of 90°C and a vacuum degree of 0.08mPa to obtain the high-purity silica sol.

[0060] The high-purity silica sol prepared in this example was characterized by scanning electron microscopy, and a scanning electron microscopy characterization image of the high-purity silica sol in Example 1 was obtained, as shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the particles of high-purity silica sol are solid spheres with a diameter of about 10 to 12 nm.

[0061] Example 2

[0062] The other conditions in Example 1 remain unchanged, and the particle size of the silicon powder is modified to 150-200 meshes to obtain the high-purity silica sol.

[0063] Example 3

[0064] The other conditions in Example 1 remain unchanged, and the initial temperature for initiating the reaction is changed to 70° C. to obtain the high-purity silica sol.

[0065] Example 4

[0066] The other conditions in Example 1 remain unchanged, and the target temperature of the initiation reaction is changed to 85° C. (i.e., the initiation reaction ends after the temperature is raised to 85° C.), thereby obtaining the high-purity silica sol.

[0067] Example 5

[0068] The other conditions in Example 2 are controlled to remain unchanged, and the modification is as follows: the polymerization reaction time (the total time from the start of water addition to the end of the polymerization reaction) is set to 6 hours to obtain the high-purity silica sol.

[0069] Example 6

[0070] The other conditions in Example 1 are controlled to remain unchanged, and the conditions are modified as follows: after the initiation reaction is completed, 240 g of water is slowly added dropwise into the three-necked flask under stirring to obtain the high-purity silica sol.

[0071] Example 7

[0072] The other conditions in Example 1 remain unchanged, and the polymerization reaction time is changed to 6 hours to obtain the high-purity silica sol.

[0073] Example 8

[0074] The other conditions in Example 1 are controlled unchanged, and the method of naturally cooling the obtained system to 60° C. after the polymerization reaction is completed is modified to the method of naturally cooling the obtained system to 50° C. after the polymerization reaction is completed, to obtain the high-purity silica sol.

[0075] Example 9

[0076] The other conditions in Example 8 are controlled to remain unchanged, and n-butyl lithium is replaced by lithium tert-butoxide. The preparation method of lithium tert-butoxide is: tert-butanol and n-butyl lithium (the molar ratio of tert-butanol to n-butyl lithium is 1:1) are mixed, and reacted at 25° C. for 1 hour to obtain lithium tert-butoxide (C4H9OLi); in addition, a nitric acid solution with a mass fraction of 65% is used to replace a sulfuric acid solution with a mass fraction of 95%, and finally the high-purity silica sol is prepared.

[0077] Example 10

[0078] The other conditions in Example 8 are controlled to remain unchanged, and n-butyl lithium is replaced by polyethylene glycol lithium. The preparation method of polyethylene glycol lithium is as follows: polyethylene glycol (PEG400) and n-butyl lithium (the molar ratio of PEG400 to n-butyl lithium is 1:1) are mixed, and the mixture is reacted at 25°C for 1 hour to obtain polyethylene glycol lithium (H(OC2H4)9OLi); in addition, a nitric acid solution with a mass fraction of 65% is used to replace a sulfuric acid solution with a mass fraction of 95% to obtain the high-purity silica sol.

[0079] Comparative Example 1

[0080] While keeping other conditions in Example 1 unchanged, the high-purity silica sol prepared in Example 1 was mixed with tert-butanol (the mass ratio of the high-purity silica sol to tert-butanol was 1:0.1-0.5) to obtain a sample to be tested.

[0081] Comparative Example 2

[0082] While keeping other conditions in Example 1 unchanged, the high-purity silica sol prepared in Example 1 was mixed with polyethylene glycol PEG400 (the mass ratio of the high-purity silica sol to the polyethylene glycol PEG400 was 1:0.1-0.5) to obtain a sample to be tested.

[0083] The silica sols prepared in Examples 1 to 10 and the samples to be tested prepared in Comparative Examples 1 to 2 were subjected to performance tests, wherein the specific gravity test was conducted according to the standard method specified in GB / T 4472-2011, and the viscosity test was conducted according to the standard method specified in GB / T 10247-2008. The performance test results of different samples are shown in Table 1.

[0084] Table 1 Performance test results of different samples

[0085]

[0086]

[0087] From the above examples, it can be seen that the present invention uses a sodium-free organic catalyst as an initiator and a single-substance silicon powder as a silicon source, generates silicic acid by reacting with water, and further polymerizes and concentrates to prepare a high-value-added sodium-free high-purity spherical silica sol. The mass fraction of silicon dioxide in the spherical silica sol is 25-40%, and the specific gravity of the silica sol at 20°C is 1.1-1.3 g / cm 3 The viscosity of the silica sol at 25°C is 10-50000 cP, and the particle size of the silica sol is 10-20 nm. The preparation method of the invention has simple process, low production cost, no environmental pollution, easy industrialization, good application prospect and huge economic benefits.

[0088] In addition, the high-purity silica sol prepared in Example 9 of the present invention has a carbon content of 5.2% (dry basis) and can be mixed and dissolved in a commercial lithium battery electrolyte such as 8335, with a conductivity of 10 -1 S / cm; Example 10 prepared high-purity silica sol, forming a gel, after drying, the melting point is 85 ℃, higher than PEG400 (64 ~ 66 ℃), the measured conductivity is 10 -2 S / cm; the conductivity of the two high-purity silica sols is much higher than that of polyethylene glycol (10 -13 S / cm), fully meeting the requirements of solid electrolyte 10 -2 The requirements of S / cm can be applied to the precursor of solid electrolyte. After adding tert-butyl alcohol to comparative example 1, the silica sol agglomerated and became completely unstable, and the battery could not be made. After adding polyethylene glycol to comparative example 2, the silica sol condensed and precipitated, and became completely unstable, and the electrical properties could not be measured. Among them, the above conductivity was tested according to the method of national standard GB / T11007-2008.

[0089] The present invention does not need to use inorganic acid to wash and regenerate the ion exchange resin, thus avoiding the defects of the existing ion exchange method of consuming a large amount of inorganic acid and washing water, reducing the discharge of a large amount of salt-containing and acid-containing wastewater, and reducing the pressure of environmental pollution. In addition, since elemental silicon is used as a silicon source and an organic catalyst is used as an initiator, the impurity removal process of sodium ion impurities in the sodium silicate raw material and the alkaline catalyst containing sodium ions is avoided, and a sodium-free ultra-high-purity high-value-added silica sol product can be prepared.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-purity silica sol, characterized in that: It includes the following steps: (1) mixing a lithium source, silicon powder and a first portion of water to initiate a reaction, and adding remaining water after the initiation reaction to perform a polymerization reaction to obtain a first product; (2) mixing the first product with an acid solution to obtain a mixed solution; filtering the mixed solution, and then concentrating the filtrate obtained by filtration to obtain the high-purity silica sol.

2. The method for preparing high-purity silica sol according to claim 1, characterized in that: The particle size of the silicon powder in step (1) is 100 to 600 mesh; The lithium source is alkyl lithium or alkoxy lithium; the alkoxy lithium includes fatty alkyl alcohol lithium or polyethylene glycol lithium; The mass ratio of the lithium source to the silicon powder is 0.5-5:100, and the mass ratio of the silicon powder to the first portion of water is 5-20:20-60.

3. The method for preparing high-purity silica sol according to claim 1 or 2, characterized in that: The initial temperature of the initiation reaction in step (1) is 60-80°C, the temperature is increased during the initiation reaction, the heating rate of the initiation reaction is 10-20°C / min, and the target temperature of the initiation reaction is 85-95°C.

4. The method for preparing high-purity silica sol according to claim 3, characterized in that: In step (1), the mass ratio of the first part of water to the remaining water is 20-60:40-80.

5. The method for preparing high-purity silica sol according to claim 4, characterized in that: The temperature of the polymerization reaction in step (1) is the same as the target temperature of the initiation reaction, and the polymerization reaction time is 2 to 10 hours.

6. The method for preparing high-purity silica sol according to claim 5, characterized in that: The acid solution in step (2) includes one or more of hydrochloric acid solution, nitric acid solution and sulfuric acid solution; The mass fraction of the hydrochloric acid solution is 8-33%, the mass fraction of the nitric acid solution is 30-70%, and the mass fraction of the sulfuric acid solution is 94-96%.

7. The method for preparing high-purity silica sol according to claim 6, characterized in that: The pH value of the mixed solution in step (2) is 0.5 to 4.5; The concentration temperature in step (2) is 80-100° C., and the concentration vacuum degree is 0.06-0.1 mPa.

8. The high-purity silica sol prepared by the method for preparing high-purity silica sol according to any one of claims 1 to 7.

9. The high-purity silica sol according to claim 8, characterized in that: Dioxygen in high purity silica sol The mass fraction of silicon dioxide is 25-40%, and the specific gravity of high-purity silica sol at 20°C is 1.1-1.3 g / cm 3 , The viscosity of the high-purity silica sol at 25° C. is 10 to 50,000 cP, and the particle size of the high-purity silica sol is 10 to 20 nm.

Citation Information

Patent Citations

  • Preparation method of ultra-high pure silica sol for capacitor

    CN104326477A

  • Simple and quick method for preparing silica sol

    CN106145123A

Cited By

  • Preparation method of rare earth catalyst for petroleum cracking

    CN121551050A